2021
DOI: 10.48550/arxiv.2110.15472
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

From KP-I lump solution to travelling waves of Gross-Pitaevskii equation

Abstract: Let q(x, y) be an nondegenerate lump solution to KP-I (Kadomtsev-Petviashvili-I) equation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…For instance, in [8](see also the references therein), it is shown that KP equation is related to the GP equation. The nondegeneracy result for the lump can then be used to construct traveling wave solutions of the GP equation with subsonic speed, with a perturbation argument; see [39].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in [8](see also the references therein), it is shown that KP equation is related to the GP equation. The nondegeneracy result for the lump can then be used to construct traveling wave solutions of the GP equation with subsonic speed, with a perturbation argument; see [39].…”
Section: Introductionmentioning
confidence: 99%